2018
DOI: 10.1371/journal.pone.0191216
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with gingipain A hemagglutinin domain of Porphyromonas gingivalis induces IgM antibodies binding to malondialdehyde-acetaldehyde modified low-density lipoprotein

Abstract: Treatment of periodontitis has beneficial effects on systemic inflammation markers that relate to progression of atherosclerosis. We aimed to investigate whether immunization with A hemagglutinin domain (Rgp44) of Porphyromonas gingivalis (Pg), a major etiologic agent of periodontitis, would lead to an antibody response cross-reacting with oxidized low-density lipoprotein (OxLDL) and how it would affect the progression of atherosclerosis in low-density lipoprotein receptor-deficient (LDLR-/-) mice. The data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
1
16
0
2
Order By: Relevance
“…The mouse plasma IgM, but not IgG, in immunized mice recognizes apoptotic Jurkat cells. The result is consistent with the opinion that IgM antibodies to MAA-LDL may have a very important role in atheroprotection by inhibiting the macrophages uptake of the oxidized LDL, and by enhancing apoptotic cell clearance [3,4]. Little is known about the role of IgM antibodies to HSP60 in the development of atherosclerosis.…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations
“…The mouse plasma IgM, but not IgG, in immunized mice recognizes apoptotic Jurkat cells. The result is consistent with the opinion that IgM antibodies to MAA-LDL may have a very important role in atheroprotection by inhibiting the macrophages uptake of the oxidized LDL, and by enhancing apoptotic cell clearance [3,4]. Little is known about the role of IgM antibodies to HSP60 in the development of atherosclerosis.…”
Section: Plos Onesupporting
confidence: 86%
“…They cross-react, respectively, with a hemagglutinin domain of gingipain protease of Pg (Rgp44) and Aa-HSP60. We have also reported that immunization with Rgp44 reduces atherosclerosis in LDL receptor-deficient (LDLR -/-) mice and that increased IgM levels to MAA-LDL may contribute to atheroprotection [4]. Therefore, Aa-HSP60-induced antibody response to MAA-LDL may cross-react with virulence factors, such as Rgp44, from Pg bacteria.…”
Section: Plos Onementioning
confidence: 97%
See 2 more Smart Citations
“…IgM that bind to these epitopes are already present before birth . A natural monoclonal IgM to MDA‐LDL has been shown to recognize arginine‐specific gingipain domains of P. gingivalis . Proteolytic enzymes of P. gingivalis , especially the arginine‐specific gingipain, are able to modify LDL particles, resulting in oxidation .…”
Section: Molecular Mimicrymentioning
confidence: 99%